Narrowing the gender digital divide in Pakistan: Mobile phone ownership and female labor force participation - Hina Amber; Bezawit Beyene Chichaibelu (Review of Development Economics, 2023)
The unprecedented growth in access to mobile phones and smartphones has opened up new possibilities in the way people live and work. However, women in developing countries are unable to take advantage of this growth due to certain factors and socio-cultural norms that give rise to the gender digital divide. In this study, using the nationally representative Pakistan Social and Living Standards Measurement Survey (2019–2020), we investigate the gender and rural–urban (female) digital divide in a country with one of the most considerable digital divides. Furthermore, we employ an instrumental variable approach to study the effect of mobile or smartphone ownership on female labor force participation. The results indicate that institutional and sociocultural norms explain most of the ownership gap of mobile or smartphones between men and women. The instrumental variable approach demonstrates that mobile or smartphone ownership increases the participation of women in the labor force. We also find that the differences between observable characteristics, especially literacy and education, explain the rural–urban digital divide among females. Considering the importance of mobile or smartphone ownership in facilitating women's labor supply decisions, providing women with digital tools and upskilling them has wider implications for their economic well-being.
Keywords: 330; decomposition; female labor force; gender digital divide; instrumental variable; mobile or smartphone; rural–urban divide